2014
DOI: 10.1007/s10719-014-9561-7
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Glyco-sialylation changes monitors oral carcinogenesis

Abstract: Alterations in cell membrane glycosylation play important role in oral carcinogenesis. The present study evaluated salivary sialylation changes i.e. total sialic acid (TSA), sialidase activity, linkage specific (α2-3 and α2-6) sialoproteins and sialyl transferase (ST) activity in controls, patients with oral precancerous conditions (OPC) and oral cancer. Subjects enrolled included 100 controls, 50 patients with OPC, 100 oral cancer patients, and 30 post treatment follow-ups. TSA was estimated by spectrophotome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…In this study, we investigated the mRNA levels of various STs (ST3GAL1, ST3GAL2, ST3GAL3, ST3GAL4, ST3GAL6, and ST6GAL1) and sialidases (NEU3) and found that all the transcripts were significantly down‐regulated in malignant tissues as compared to normal tissues. Although in our previous reports, we found increased levels of STs and sialidase enzyme activity in malignant tissue, serum, and saliva of oral cancer patients . However, in this study the non‐malignant and microscopically uninvolved part of tumor showed enhanced mRNA levels of STs and sialidase.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…In this study, we investigated the mRNA levels of various STs (ST3GAL1, ST3GAL2, ST3GAL3, ST3GAL4, ST3GAL6, and ST6GAL1) and sialidases (NEU3) and found that all the transcripts were significantly down‐regulated in malignant tissues as compared to normal tissues. Although in our previous reports, we found increased levels of STs and sialidase enzyme activity in malignant tissue, serum, and saliva of oral cancer patients . However, in this study the non‐malignant and microscopically uninvolved part of tumor showed enhanced mRNA levels of STs and sialidase.…”
Section: Discussioncontrasting
confidence: 89%
“…Carbohydrate determinants present on the cancer cell surface contain sialylated and/or fucosylated structures. Synthesis of these carbohydrate determinants is regulated by a set of STs and fucosyltransferases (FUTs) . Hypersialylation is often found on cell surface glycoproteins of malignant cells and also found to be associated with the malignant phenotype and metastatic potential of different cancers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] Similarly, Vajaria et al reported on salivary sialylation changes where the levels of sialic acid were increased in precancerous and oral cancer. [26] Sanjay et al reported a higher level of salivary total protein, total sugar, and sialic acid in OSCC when compared to normal healthy individuals. According to their study, Salivary sialic acid levels were significantly elevated in well-differentiated squamous cell carcinomas than in moderately differentiated squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%